Somatic chromosome number and ploidy level in three Curcuma spp. from Bangladesh (Dhaka University Journal of Biological Sciences, 2021)
Three Curcuma L. species were investigated cytogenetically which represent diversed staining pattern of heterochromatins in interphase nuclei and prophase chromosomes with orcein staining. Curcuma longa and C. caesia were found to possess 2n = 3x = 63 somatic chromosomes whereas 2n = 2x = 42 chromosome number in C. zedoaria is reported for the first time from Bangladesh. Total chromosome length recorded in C. longa, C. caesia and C. zedoaria were 145.08 ± 2.85 μm, 164.93 ± 4.29 μm and 97.78 ± 2.41 μm, respectively. This was the first attempt to measure the length of the chromosomes for these species. The experiment confirmed the basic chromosome number x = 21 with triploid (C. longa, C. caesia) and diploid (C. zedoaria) Curcuma plants. Polyploidy could be employed in the evolution and diversification of the genus Curcuma, which is an essential factor to characterize the species of this genus.Dhaka Univ. J. Biol. Sci. 30(2): 133-140, 2021 (July)